2013
DOI: 10.1016/j.ijvsm.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of infectious bronchitis viruses isolated from broiler and layer chicken farms in Egypt during 2012

Abstract: One of the major problems of avian infectious bronchitis virus (IBV) is the frequent emergence of new variants. In the present study 205 tracheal swabs and organs were collected from broilers and layers chicken farms during January to August 2012 from 19 governorates all over Egypt. The chickens demonstrated respiratory signs and mortality. Out of the examined samples, 130 of which (about 64%) of suspected farms were positive for IBV with real time RT-PCR. 13 IBV-positive samples were selected for further isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 19 publications
2
25
1
Order By: Relevance
“…The current situation of IB infections in Egypt seems to be the result of a continuing evolution starting with infections caused by Egyptian variant I since 2001, Egyptian variant II since 2011, and Mass-like strains since 2006 (Abdel-Moneim et al, 2012;Selim et al, 2013). Tracheal ciliostasis is one of the early and characteristic pathogenetic sequelae of IBV infection (Cook et al, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…The current situation of IB infections in Egypt seems to be the result of a continuing evolution starting with infections caused by Egyptian variant I since 2001, Egyptian variant II since 2011, and Mass-like strains since 2006 (Abdel-Moneim et al, 2012;Selim et al, 2013). Tracheal ciliostasis is one of the early and characteristic pathogenetic sequelae of IBV infection (Cook et al, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…In May 2012, the virus designated IBV/chicken/Egypt/VRLCU154/2012, isolated from tracheal swabs from a vaccinated broiler flock and it was in close relationship with the IBV isolate IS/1494/06 (Hussein et al, 2014). Another study of IBVs isolated from broiler and layer chicken farms in Egypt revealed that 11 out of 13 isolates had a close relationship with Israeli variants (IS/885 and IS/1494/06), with nucleotide homology reaching up to 89.9% and 82.3%, respectively (Selim et al, 2013). In Libya, 12 IBV strains obtained from broiler flocks with respiratory disease and high mortality were differentiated by sequencing of the S1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular monitoring of IBV strains circulating in Iran revealed that most detected strains belonged to IS/720 and Var2 (both GI-23), which were responsible for 18.4% and 17.2% of clinical cases of IB, respectively (Hosseini et al, 2015). In Egypt, this IBV lineage has been circulating since 2010 and by 2012 has dominated among other strains (Hussein et al, 2014;Selim et al, 2013;Zanaty et al, 2016). In 2011 and 2012 the GI-23 strains has been identified in Turkey and Libya, respectively (Awad et al, 2014;Kahya et al, 2013;Yilmaz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Later on, the presence of IBV GI-23 was found in Saudi Arabia, Kuwait, Bahrain, Armenia, and since 2015 also in Russia, Lithuania and Ukraine (personal information from Ashash U., Israel). The IBV GI-23 lineage was detected in unvaccinated and vaccinated broilers, layers and broiler breeders and caused respiratory system disease, kidney damage and drop in egg production (Hussein et al, 2014;Kahya et al, 2013;Selim et al, 2013). Intensive international trade, uncontrolled movement of people and animals as well as of wild birds across the borders of the Middle Eastern countries were suspected as the cause of the spread of the GI-23 lineage (Domanska-Blicharz et al, 2014;Hussein et al, 2014;Kahya et al, 2013).…”
Section: Introductionmentioning
confidence: 99%